Falling as a strategy to decrease knee loading during landings: Implications for ACL injury prevention. (26th August 2020) - Li, Ling; Baur, Marten; Baldwin, Kevin; Kuehn, Taylor; Zhu, Qin; Herman, Daniel; Dai, Boyi
Abstract: Anterior cruciate ligament (ACL) injuries often occur when individuals land primarily on a single leg. Falling has been proposed as a potential strategy to decrease knee loading during landings. The purpose of this study was to compare impact forces, knee angles, and knee moments during natural landings, soft landings, and landings followed by falling after forward and vertical jumps, each under single or double-leg conditions. Sixteen male and sixteen female participants (age: 22.0 ± 2.9 years) completed each landing condition while kinematics and ground reaction forces were collected. In the natural landing condition, participants landed as they would in a sport setting. In the soft landing condition, participants landed as softly as possible with increased knee and hip flexion. In the falling condition, participants landed softly and then fell forward or backward onto a mat after forward and vertical jumps, respectively. The falling condition demonstrated the greatest initial and peak knee flexion angles, the least peak vertical ground reaction forces, and the least peak knee extension and adduction moments compared to the natural landing and soft landing conditions. The soft landing condition resulted in similar changes in landing mechanics compared to the natural landing, but the effect was limited for single-leg landings compared to double-leg landings. When the sports environment allows, falling appears to be a potential strategy to decrease knee loading when individuals must land on a single leg with sub-optimal body postures. Future studies are needed to develop progressive training of effective and safe falling techniques.